2016
DOI: 10.1083/jcb.201507042
|View full text |Cite
|
Sign up to set email alerts
|

TOPBP1 regulates RAD51 phosphorylation and chromatin loading and determines PARP inhibitor sensitivity

Abstract: TOPBP1 acts in homologous recombination repair, impacts the response to chemotherapeutic agent olaparib, and exhibits aberrant patterns in subsets of human ovarian carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 29 publications
(38 reference statements)
8
92
0
Order By: Relevance
“…[49][50][51][52][53] Though detailed mechanisms remain to be elucidated, recent studies suggest that TopBP1 executes these functions by interacting with specific partner proteins. One study found that human TopBP1 binds to Pololike kinase and stimulates phosphorylation of the recombinase Rad51 at serine 14, a modification important for Rad51 recruitment to chromatin and recombination initiation.…”
Section: Dpb11 and Homologs Function In Recombinational Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…[49][50][51][52][53] Though detailed mechanisms remain to be elucidated, recent studies suggest that TopBP1 executes these functions by interacting with specific partner proteins. One study found that human TopBP1 binds to Pololike kinase and stimulates phosphorylation of the recombinase Rad51 at serine 14, a modification important for Rad51 recruitment to chromatin and recombination initiation.…”
Section: Dpb11 and Homologs Function In Recombinational Repairmentioning
confidence: 99%
“…One study found that human TopBP1 binds to Pololike kinase and stimulates phosphorylation of the recombinase Rad51 at serine 14, a modification important for Rad51 recruitment to chromatin and recombination initiation. 53 Others studies have shown that TopBP1 aids the resolution of DNA non-disjunctions by recruiting the scaffold SLX4 and Topoisomerase 2A to chromatin. 52,54 Furthermore TopBP1 can promote DNA synthesis at under-replicated regions during mitosis by unknown mechanisms.…”
Section: Dpb11 and Homologs Function In Recombinational Repairmentioning
confidence: 99%
“…In this work, the authors first identified TOP BP1 as a hit in a high-content RNAi screen for proteins whose depletion resulted in higher toxicity after olaparib treatment in osteosarcoma cells, which suggests that loss or inactivation of TOP BP1 predicts the response of cancer cells to this drug. Moudry et al (2016) observed that RNAi-mediated knockdown of TOP BP1 in cancer cells treated with olaparib increased the level of DNA damage and induced DNA DSB markers. The researchers subsequently examined whether olaparib sensitivity reflected defective HR in TOP BP1-depleted cells by measuring HR activity through several parameters and confirmed that TOP BP1-depleted cells showed reduced HR activity.…”
mentioning
confidence: 99%
“…Although the work of Moudry et al (2016) is the first to show a clear role for TOP BP1 in RAD51 loading, studies in budding yeast have proposed links between the TOP BP1 orthologue Dpb11 and HR-mediated repair. It was shown that the temperature-sensitive dpb11-1 mutant displays a sensitivity to DNA damage that is not further increased by deletion of RAD51, suggesting that Dpb11 functions in HR repair (Ogiwara et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation